Efficient Photoreduction of Diluted CO2 to Tunable Syngas by Ni−Co Dual Sites through d‐band Center Manipulation. Issue 42 (12th September 2022) - Qian, Gan; Lyu, Wenyuan; Zhao, Xin; Zhou, Jingyi; Fang, Ruiqi; Wang, Fengliang; Li, Yingwei
Abstract: Photocatalytic conversion of CO2 into syngas is a promising way to address the energy and environmental challenges. Here we report the integration of Ni−Co dual sites on Ni doped Co3 O4 ultrathin nanosheets assembled double‐hollow nanotube (Ni−Co3 O4 NSDHN) for efficient photoreduction of low‐concentration CO2 . Quasi in situ spectra and density functional theory calculations demonstrate that the declining of d ‐band center of Ni−Co dual sites enables the electrons accumulation in the dxz / dyz ‐2π* and dz2 ‐ 5 σ orbitals. As a result, the binding strength of *CO is weakened and the *H adsorption site is modulated from metal sites to an oxygen site. Remarkably, Ni−Co3 O4 NSDHN exhibits superior diluted CO2 photoconversion activity and controllable selectivity under the irradiation of visible light or even natural sunlight. A syngas evolution rate of 170.0 mmol g −1  h −1 with an apparent quantum yield of 3.7 % and continuously adjustable CO/H2 ratios from 1 : 10 to 10 : 1 are achieved. Abstract : The binding strength of *CO and *H can be collectively regulated through d‐band center manipulation over Ni−Co dual sites, enabling the kinetic controls of both the CO2 reduction and hydrogen evolution processes. The as‐obtained Ni doped Co3 O4 ultrathin nanosheets exhibit superior activity and controllable selectivity in the photoconversion of diluted CO2 to syngas under the irradiation of visible light or even natural sunlight.